Spintronics: Realistic Large‐Scale Modeling of Rashba and Induced Spin–Orbit Effects in Graphene/High‐Z‐Metal Systems (Adv. Theory Simul. 10/2018). Issue 10 (4th October 2018) - Voloshina, Elena; Dedkov, Yuriy
Abstract : The correct modeling of graphene‐metal interfaces is crucial for the description of different properties of these systems. In article number1800063, Elena Voloshina and Yuriy Dedkov present large‐scale super‐cell calculations used for the description of electronic and spin structures of different graphene/high‐Z‐metal systems. This study critically analyzes many recent discrepancies in the description of graphene/metal systems and paves the way for the use of graphene in spintronics.